Roles of Il-36 in the Pathogenesis of Inflammatory Bowel Disease in a Sample of Iraqi Patients - Zahraa F. Ibraheem, Hanan Y. Muhsin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: IBD (Inflammatory bowel disease) is a chronic inflammatory condition that affects the intestines., in which cytokines are thought to have a role in the etiology and pathophysiology. IBD is divided into two types: Ulcerative Colitis (UC), and Crohn’s Disease (CD). Aim of the study: The current study examined the level of, IL-36 in the blood of sixty IBD Iraqi patients (30 CD, 30 UC, and 30 HC). The concentrations were correlated with Age, age at onset, body mass index (BMI), cigarette-smoking status, disease duration, gender, symptoms, and extra-intestinal features. Result: The findings revealed that IL-36 level for UC & CD patients have been significantly higher than the healthy control). However, there was a significant difference in IL-36 levels between UC and CD patients p. When UC and CD patients were divided into subgroups based on certain features, it was discovered that IL-36 was significantly increased in CD patients with disease duration >10 year compared to UC patients). In addition, It was in BMI underweight, CD patients significantly increased compared, to UC patient. while in CD patient there was a significant difference between patients with BMI underweight compared to patients with BMI obese). In the case of, non-smoker patients there was a significant increase in CD patients compared to UC). Conclusion: the findings suggest that IL-36 has a role in the etiology & pathophysiology of IBD. Keywords: IBD, CD, UC, HC, IL-36, Disease duration, Body mass index, cigarette-Smoking, healthy control, Crohn’s Disease, Ulcerative Colitis, and Inflammatory Bowel Disease.